Effects of the Age of Newborn Pigs Receiving an Iron Injection on Suckling and Subsequent Nursery Performance and Blood Criteria - H. Williams; C. D. Roubicek; J. M. DeRouchey; J. C. Woodworth; S. S. Dritz; M. D. Tokach; R. D. Goodband; A. Holtcamp (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 324 newborn pigs (DNA 241 × 600, initially 3.56 ± 0.10 lb body weight (BW)) were used in a 80-d study evaluating the effects of Fe injection timing after birth on suckling and subsequent nursery pig performance and blood criteria. GleptoForte (Ceva Animal Health, LLC., Lenexa, KS) contains gleptoferron, which is an Fe macromolecule complex that is used as an injectable Fe source for suckling piglets. A total of 27 litters were used with the number of pigs per sow equalized on each day of farrowing. Two d after birth, all piglets were weighed, and six barrows and six gilts were allotted to 1 of 6 treatments within litter in a randomized complete block design. Treatments consisted of a negative control receiving no Fe injection or 200 mg of injectable Fe from GleptoForte provided in a single injection on d 2, 4, 6, 8, or 10 after birth. Piglets were weighed on d 2, 12, and weaning (d 21) to calculate average daily gain (ADG) during farrowing. Piglets were bled on d 2, 12, and 21 to determine blood Fe status. The blood criteria evaluated to determine Fe status were: hemoglobin (Hgb), hematocrit (Hct), serum Fe, and total Fe binding capacity (TIBC). Pigs were weaned at approximately 21 d of age and allotted to pens based on previous Fe treatment with BW balanced across all pens within a treatment with 5 or 6 pigs per pen and 10 pens per treatment. Common diets were fed throughout the nursery in 3 phases. Pigs and feeders were weighed on d 28, 35, 42, 48, 55, 62, and 80 after birth to determine ADG, average daily feed intake (ADFI), and feed efficiency (F/G). Pigs were bled on d 21 (weaning) and 35 after birth to determine blood Fe status. In farrowing, increasing the age that piglets received a 200 mg Fe injection until 4 or 6 d after birth provided marginal evidence for an improvement (quadratic;P= 0.065) in ADG. Not providing an Fe injection resulted in marginal evidence for a decrease (P= 0.070) in overall ADG and decreased (P= 0.001) d 21 BW compared to all other treatments. For the nursery period, increasing the age of piglets receiving a 200 mg Fe injection from 2 to 4 or 6 d after birth improved (quadratic;P= 0.013) d 80 ending BW with a decrease in BW when Fe was provided after d 6. Significant treatment × day interactions (P= 0.001) were observed for hemoglobin (Hgb) and hematocrit (Hct). The interactions occurred because pigs injected with 200 mg Fe on d 2, 4, 6, or 8 after birth had increasing values until d 12 after birth, while pigs not receiving an Fe injection or pigs receiving a 200 mg Fe injection on d 10 after birth had decreasing values to d 12 after birth. All pigs receiving a 200 mg Fe injection after birth had increased values from d 12 to 21 and then slightly decreased to d 35 after birth, while pigs not receiving an Fe injection had decreased values from d 12 to 21 and then increasing values to d 35 after birth. In summary, providing a 200 mg Fe injection on d 4 or 6 after birth provided the greatest preweaning growth performance and body weight at the end of the nursery phase. Providing a 200 mg Fe injection on d 6 after birth provided the greatest blood Fe status up to weaning, but there was no evidence of difference in blood Fe status in the nursery when administering a 200 mg Fe injection within 10 d after birth.
Keywords: Fe; gleptoferron; growth performance; nursery; timing